In utero exposure to cigarette smoke and effects across generations: A conference of animals on asthma. Issue 11 (30th October 2018) - Hammer, Barbara; Wagner, Christina; Divac Rankov, Aleksandra; Reuter, Sebastian; Bartel, Sabine; Hylkema, Machteld N.; Krüger, Arne; Svanes, Cecilie; Krauss‐Etschmann, Susanne
Summary: Background: The prevalence of asthma and chronic obstructive pulmonary disease (COPD) has risen markedly over the last decades and is reaching epidemic proportions. However, underlying molecular mechanisms are not fully understood, hampering the urgently needed development of approaches to prevent these diseases. It is well established from epidemiological studies that prenatal exposure to cigarette smoke is one of the main risk factors for aberrant lung function development or reduced fetal growth, but also for the development of asthma and possibly COPD later in life. Of note, recent evidence suggests that the disease risk can be transferred across generations, that is, from grandparents to their grandchildren. While initial studies in mouse models on in utero smoke exposure have provided important mechanistic insights, there are still knowledge gaps that need to be filled. Objective: Thus, in this review, we summarize current knowledge on this topic derived from mouse models, while also introducing two other relevant animal models: the fruit fly Drosophila melanogaster and the zebrafish Danio rerio . Methods: This review is based on an intensive review of PubMed‐listed transgenerational animal studies from 1902 to 2018 and focuses in detail on selected literature due to space limitations. Results: This review gives a comprehensive overview of mechanistic insights obtained in studies with the three species, while highlighting the remaining knowledge gaps. We will further discuss potential (dis)advantages of all three animal models. Conclusion/Clinical Relevance: Many studies have already addressed transgenerational inheritance of disease risk in mouse, zebrafish or fly models. We here propose a novel strategy for how these three model organisms can be synergistically combined to achieve a more detailed understanding of in utero cigarette smoke‐induced transgenerational inheritance of disease risk.